2016
DOI: 10.1371/journal.pgen.1006351
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Ciliopathies Reveal Specific Requirements for GLI Proteins during Development of the Facial Midline

Abstract: Ciliopathies represent a broad class of disorders that affect multiple organ systems. The craniofacial complex is among those most severely affected when primary cilia are not functional. We previously reported that loss of primary cilia on cranial neural crest cells, via a conditional knockout of the intraflagellar transport protein KIF3a, resulted in midfacial widening due to a gain of Hedgehog (HH) activity. Here, we examine the molecular mechanism of how a loss of primary cilia can produce facial phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 78 publications
2
58
0
Order By: Relevance
“…We found that the transcriptional effectors of the HH pathway, the GLI proteins, did not undergo proper post-translational processing in the frontonasal prominence. We specifically found increased GLI2/3 full-length isoforms were produced at the expense of the truncated repressor isoforms (Chang et al, 2016). These data suggested that the transcriptional targets of the HH pathway in NCCs might not be appropriately regulated in the midface.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We found that the transcriptional effectors of the HH pathway, the GLI proteins, did not undergo proper post-translational processing in the frontonasal prominence. We specifically found increased GLI2/3 full-length isoforms were produced at the expense of the truncated repressor isoforms (Chang et al, 2016). These data suggested that the transcriptional targets of the HH pathway in NCCs might not be appropriately regulated in the midface.…”
Section: Discussionmentioning
confidence: 95%
“…1A, B), a duplicated nasal septum, and aglossia (Brugmann et al, 2010; Chang et al, 2016; Millington et al, 2017). While each of these phenotypes was striking and severe, they were not necessarily surprising, as neural crest cells (NCCs) contribute significantly to the development of each of these structures (Chai et al, 2000; Danielian et al, 1998; Noden and Trainor, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, Chang et al demonstrate that disruption of cilia function leads to an increase in the amount of full-length GLI2 and GLI3 in the nucleus, thus shifting the ratio of GLIA:GLIR toward the activator form [6]. This was partially rectified by increasing the amounts of GLI3R.…”
Section: Cilia and The Balance Of Gli Functionsmentioning
confidence: 99%
“…Altogether, this suggests that the phenotypic interpretation of HH signaling changes is more complicated than a simple on/off mechanism. In this issue, Chang et al mutate the intraflagellar transport proteins Ift88 and Kif3a in the mouse neural crest, comparing the phenotypes to those associated with functional mutations in the HH effectors Gli2 and Gli3 [6]. In doing so, they clarify the molecular basis for facial widening in ciliopathies and uncover a novel in vivo requirement for GLI-mediated transcriptional repression.…”
Section: Cilia and Developmental Roles For Hh Signalingmentioning
confidence: 99%